MODELING OF STRESSED-DEFORMED STATE AND RESIDUAL STRESSES IN TWO-LAYER CYLINDER - Yu. M. Pleskachevsky; Yu. A. Chigarevа (Наука и техника, 2014)
The paper presents a calculation method for thermo-elasto-plastic stressed-deformed state in two-layer cylindrical bodies due to abrupt temperature changes on outer load-free boundary. The boundaries of plastic zones at various relations correlations between stress-strain properties of the internal and external cylinders and distribution of residual stresses after temperature unloading have determined in the paper.